Ethnobotany of fuel species traded in the Ribera Platense, Buenos Aires, Argentina - Doumecq, María Belén; Arenas, Patricia Marta; Hurrell, Julio Alberto (Ethnobotany Research and Applications, 2020)
Background. The use of firewood is a very current topic worldwide. More than two billion people in different parts of the world frequently use firewood and other forms of biomass to cook and get heat (CIFOR 2012, FAO 2019). In South America, fuel plants are still an essential part of subsistence economies, especially in areas of high climate strictness (Cardoso 2013, Jiménez Escobar & Martínez 2019, Morales et al. 2018, Nascimiento et al. 2019, Ramos et al. 2008a). In Argentina, the main contributions on the use of firewood come from Patagonia (Arré et al. 2015, Cardoso 2013, Morales et al. 2017a,b, 2018) and the provinces of Salta (Otegui 2016), Catamarca (Jiménez Escobar & Martínez 2019) and Córdoba (Martínez 2015). Most of these studies have been conducted in rural communities. In Buenos Aires province there are studies developed in the Río de la Plata riverside. This is a complex area with diverse environmental and cultural situations that make possible the survey of the Local Botanical Knowledge (LBK). This knowledge guides the selection and use of fuel plants within the local urban, peri-urban, and rural biocultural scenarios (Doumecq 2015, 2016, Doumecq & Arenas 2018, Doumecq & Riat 2017, Stampella et al. 2016). The general objective of this research is to analyze and compare the LBK of the firewood sellers of the study area in its northern sector, the Buenos Aires Metropolitan Area (BAMA), and the southern sector, the “Parque Costero del Sur” (PCS) and surroundings. Methods. Usual ethnobotanical methods and techniques with a qualitative approach, such as participating observation, free listings, and open and semi-structured interviews, were applied. The sellers interviewed were selected through the "snowball" technique (Alexíades 1996, Albuquerque & Lucena 2004, Albuquerque et al., 2014ab, Bernard 2000, Martin 1995). An exhaustive search of local firewood sale sites on the Internet complemented that selection. Thirty-one firewood and coal sale sites (25 in the BAMA and 6 in the PCS) were surveyed. In all cases, prior informed consent was achieved. The information obtained in the field works was recorded in notebooks and through audiovisual media. Herbarium and wood materials of the mentioned ethnotaxa were collected together with the interviewees. Furthermore, samples of commercialized firewood were obtained to be taxonomically identified. All the materials were deposited in the ethnobotanical collections of the Laboratorio de Etnobotánica y Botánica Aplicada. Results and discussion. The interviewees are people between 25 and 70 years old, mostly natives from the study area, of both sexes but mainly males (77, 4 %), so that the local practices associated with the firewood extraction and sale it could correspond to a gender issue, as was indicated for Brazil by Ramos et al. (2008b). LBK transmission about woodworking activity is diverse in the study area. In the urban and peri-urban areas, in particular, knowledge is diffused mainly in a simultaneous way and in multiple directions at the same time. In Argentina, the collection of firewood for domestic use is carried out interchangeably by people of both sexes (Cardoso 2013, Doumecq 2019, Jiménez Escobar & Martínez 2019, Morales et al. 2017), while the collection for commercialization is carried out by men (Arré et al. 2015), coinciding with the results obtained here. In the BAMA, the interviewees mainly obtain firewood through the purchase (55%), the extraction of wood from the area (32%), and the recycling of disused wood (13%). These three strategies are often combined. In the PCS, the supply of firewood outside the park comes mainly from the extraction, and inside the park comes exclusively from the purchase (the extraction is prohibited within the park according to current legislation). The main season for extracting firewood is summer, as was recorded in other parts of the world (Miah et al. 2003, Ramos & Albuquerque 2012, Ramos et al. 2008b). The extraction sites in the BAMA are public or private green spaces. In the PCS, the most frequent sources of supply are the implanted Eucalyptus forests. The peridomestic forestations generally constitute a multipurpose strategy in rural contexts, one of these purposes being the firewood supply (Cardoso & Ladio 2011). Besides, firewood from hardwood species like "quebracho colorado" (Schinopsis balansae) and "itín" (Prosopis kuntzei), which come from northern Argentina, is bought for sale. According to most of the interviewees, the sale of firewood has decreased in the last 30 years, because the consumers modified the way to heat their houses, preferring the use of gas and/or electricity. In the BAMA, 44% of the interviewees use firewood in their house, within the PCS 100% uses firewood, and outside the park, only 33%. Interviewees who do not use firewood argue that they prefer to use natural gas. Those who use firewood do so due to lack of access to gas service, although some prefer to use firewood instead of gas because they consider that firewood generates heat of better quality. The most commonly used species are "quebracho colorado" and "eucalyptus". According to some authors Cardoso (2013), Cardoso et al. (2012, 2013), Arré et al. (2015), Morales et al. (2017a), the main destination for firewood is the household heating and to a lesser extent for cooking. In total, 36 ethnotaxa marketed as firewood were surveyed, of which 33 were mentioned in the BANA and 20 in the PCS. The most widely used species are exotic, unlike that found in other studies conducted in Argentina where the native species predominate (Cardoso et al. 2013, Fernández 2017, Jiménez Escobar & Martínez 2019, Morales et al. 2017a,b). Local sellers consider as good firewood the ethnotaxa that have hard woods that produce good embers, and good heat and flame emission. To a lesser extent, it is valued the wood that emits little smoke, no sparks or resin. According to the literature, preferred ethnotaxa have hard and heavy woods and their use as firewood is widely known. In the BAMA, the most sold ethnotaxa are also the preferred: "quebracho colorado" and "itín". In the PCS the most sold is the "eucalyptus", and the preferred are "tala" (Celtis tala) and "coronillo" (Scutia buxifolia), both native species protected inside the park according current legislation. In this local context, the interviewees avoid making the extraction of firewood within the PCS to elude complications, opting for the purchase or the extraction of firewood outside the PCS. In this frame, exotic species emerge as an alternative for local use due to the lack of access to native species. Conclusions. From the comparative analysis of the results obtained in BAMA and PCS, similarities and differences emerged. Likewise, differences were found inside the PCS. The sale of firewood in both BAMA and PCS is an activity carried out mainly by men, responding to a gender issue. The LBK transmission about the activity linked to firewood is diverse both in BAMA and PCS. In the BAMA, a greater number of sale sites were surveyed, as well as of tools used, forms of supply, commercialized ethnotaxa, and ways to classify and order them, in regards to the PCS. In general, sellers consider that the sale of firewood has decreased, a fact that they attribute to consumers preferring to use gas and/or electricity to heat their households. Also, a small percentage of the interviewees use firewood for heating. In both BAMA and PCS, there is a correlation between the physical characteristics of the wood and the preferences of the sellers, but the preferred ethnotaxa differ. In the BAMA, the most sold ethnotaxa are "quebracho colorado", "itín" and "eucalyptus". The first two are also the most valued as firewood and come from northern Argentina. In the PCS, the ethnotaxa preferred by the sellers are "tala" and "coronillo”. However, the most sold is "eucalyptus" due to the native species firewood extraction restrictions inside the PCS. Therefore, the availability and access to the species are factors that condition the use of the same, and not necessarily the preferred species are always the most used. In this context, exotic species emerge as an alternative for local use due to the lack of access to native species. Key words: firewood, firewood and coal stores, Local Botanical Knowledge, Parque Costero del Sur, Buenos Aires Metropolitan Area.